PERTANGGUNGJAWABAN PIDANA ILLEGAL LOGGING (PEMBALAKAN LIAR) SEBAGAI KEJAHATAN KEHUTANAN BERDASARKAN UNDANG-UNDANG NO. 41 TAHUN 1999 TENTANG KEHUTANAN DAN UNDANG-UNDANG NO. 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN - Ramsi Meifati Barus; Alvi Syahrin; Syamsul Arifin; Muhammad Hamdan (Universitas Sumatera Utara, 2015)
ABSTRACT Continuous destruction of natural forest has caused the decrease in the forest area. The problem of criminal act in forestry, especially illegal logging, is a very complicated problem to be coped with since the criminal act is very serious, well-organized, and has inter-state range. The people’s lack of knowledge in the importance of forest for human benefit and the weakness of law has caused the complexity of any effort to handle illegal logging. Law No. 14/1999 on Forestry has not yet formulated the definition of illegal logging so that it causes multi-interpretation. Besides that, there are many weaknesses in the previous legal provisions which cause the prevention and the eradication become complicated. Therefore, Law No. 18/2013 on the Prevention and the Eradication was established. The result of the research showed that the criminal elements of illegal logging were found in Article 12 points a, b, c, d, e, f, and g, and in Article 19 points a, b, c, d, and f of Law No. 18/2013. Criminal responsibility of the perpetrators of illegal logging individually and corporately, either intentionally or because of negligence has been formulated in Articles 82 up to 85, in Article 94, and in Article 98. The reasons for annulling the criminal act is found in Article 11, paragraph (3) and in Article 13, paragraph (2) of Law No. 18/2013. Keywords: Criminal Responsibility, Illegal Logging